2012
DOI: 10.1103/physrevlett.108.236104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Motion on the Rotational Quadrupole Alignment Parameter ofD2Reacting on Cu(111)

Abstract: Ab initio molecular dynamics (AIMD) calculations using the specific reaction parameter approach to density functional theory are presented for the reaction of D 2 on Cu(111) at high surface temperature (T s ¼ 925 K). The focus is on the dependence of reaction on the alignment of the molecule's angular momentum relative to the surface. For the two rovibrational states for which measured energy resolved rotational quadrupole alignment parameters are available, and for the energies for which statistically accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(175 citation statements)
references
References 29 publications
(73 reference statements)
7
160
2
Order By: Relevance
“…Thus, our calculations cannot account for any possible influence of phonon excitations/deexcitations on the survival probabilities. Here, we should point out that although it has been previously shown 65 that including phonons may lead to absolute values in quantitative agreement with experimental data (when the same surface is considered), the qualitative behavior is essentially the same. Therefore, taking into account this fact and the huge computational cost of including, properly, surface motion, in this work, we stick to the use of surface static approximation.…”
Section: Resultssupporting
confidence: 61%
“…Thus, our calculations cannot account for any possible influence of phonon excitations/deexcitations on the survival probabilities. Here, we should point out that although it has been previously shown 65 that including phonons may lead to absolute values in quantitative agreement with experimental data (when the same surface is considered), the qualitative behavior is essentially the same. Therefore, taking into account this fact and the huge computational cost of including, properly, surface motion, in this work, we stick to the use of surface static approximation.…”
Section: Resultssupporting
confidence: 61%
“…[36,37]. Each sticking probability point has been determined from the computation of a set of 400 NV E trajectories (constant number of atoms, volume and total energy), representing single molecule-surface collisions.…”
Section: Methodsmentioning
confidence: 99%
“…However, the computational cost of AIMD limited these first studies to a few explorative trajectories. With the growth of computational power and the development of efficient algorithms, the use of AIMD to perform statistically relevant calculations of sticking probabilities for gas-surface reactions has recently become possible [35][36][37]. Advantages of this method lie in the 'on-the-fly' computation of the forces, since this strategy bypasses the need of pre-calculating and fitting a PES, with the possibility to model the effect of surface phonons through the inclusion of the motion of the surface atoms.…”
Section: Introductionmentioning
confidence: 99%
“…No large non-adiabatic effects were found in these dynamics calculations, suggesting that the BornOppenheimer approximation works well for these systems. The validity of the static surface approximation has been tested recently for H 2 dissociation on Cu(111) using ab initio molecular dynamics (AIMD) calculations, 39 in which surface atoms in 3 layers of a 2 × 2 unit cell were allowed to move, and static corrugation model (SCM) calculations, 40 which excluded energy exchange with the surface but included the displacement of surface atoms and surface expansion effects. In these studies, good agreement was found between static surface calculations and calculations at the experimental surface temperature (T s = 120 K).…”
Section: A Dynamical Modelmentioning
confidence: 99%
“…The surface temperature used in the experiments, T s = 180 K, 31 is rather low. In ab initio molecular dynamics calculations 39 and static corrugation model calculations, 40 almost no effects were found for H 2 dissociating on Cu(111) at a surface temperature T s = 120 K. While the surface temperature for the molecular beam experiments on H 2 dissociation on Ru(0001) was slightly higher, the experimentalists did not find surface temperature effects down to T s = 140 K. 31 Furthermore, the lowest barriers in the H 2 on Ru(0001) system are further away from the surface than was the case for H 2 on Cu(111), suggesting a weaker coupling between H 2 and surface degrees of freedom. Finally, energy exchange is not expected to be important for this system due to the large mass mismatch between a H 2 molecule and a ruthenium atom.…”
Section: Scattering and Reaction At Off-normal Incidencementioning
confidence: 99%